Fenomena Komodifikasi Agama dalam Dakwah Islam di Hotel: Studi kasus Terhadap Ustad Hilman Fauzi - Tirta Wibawa, Agung; Rahman Hakim, Hari (Da'watuna: Journal of Communication and Islamic Broadcasting, 2026)
ABSTRACT. The phenomenon of contemporary Islamic da'wah has undergone a significant transformation, shifting from traditional religious spaces to modern public venues such as luxury hotels. This study examines the da'wah practices of Ustadz Hilman Fauzi as a case study to understand the process of religious commodification within an urban context. Employing a descriptive qualitative approach and a case study method, data were collected through observation, interviews, and visual documentation. The findings reveal that da'wah activities conducted in hotel settings combine religious values with modern lifestyle elements, leading to the commodification of religious symbols. While this practice contributes positively to expanding the reach of da'wah, it also poses risks of social exclusivity and the dilution of spiritual meanings. Da'wah increasingly becomes part of a consumer culture that is aesthetically packaged and targeted toward specific social segments. This study contributes to the discourse on contemporary Islamic da'wah and highlights the importance of maintaining a balance between communication innovation and authentic spiritual values. ABSTRAK. Fenomena dakwah Islam kontemporer menunjukkan pergeseran signifikan, dari ruang-ruang tradisional ke ruang publik modern seperti hotel berbintang. Penelitian ini mengkaji praktik dakwah Ustadz Hilman Fauzi sebagai studi kasus untuk memahami proses komodifikasi agama dalam konteks urban. Menggunakan pendekatan kualitatif deskriptif dan studi kasus, data dikumpulkan melalui observasi, wawancara, dan dokumentasi visual. Hasil penelitian menunjukkan bahwa dakwah di hotel menghadirkan kombinasi nilai religius dan gaya hidup modern, yang mengarah pada komodifikasi simbol-simbol agama. Praktik ini memunculkan sisi positif berupa perluasan jangkauan dakwah, namun juga menimbulkan risiko eksklusivitas sosial dan pendangkalan makna spiritual. Dakwah menjadi bagian dari budaya konsumsi yang dikemas estetis dan segmentatif. Penelitian ini memberikan kontribusi terhadap kajian dakwah kontemporer dan menekankan pentingnya menjaga keseimbangan antara inovasi komunikasi dan nilai spiritual yang otentik.